Breeding and quality of soft-textured durum wheat - Gazza L.; Sgrulletta D.; Cammerata A.; Gazzelloni G.; Galassi E.; Pogna N. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
. Puroindolines A (PIN-A) and B (PIN-B) encoded by genes Pina-D1 and Pinb-D1 on chromosome 5DS are the principal determinant factors of kernel hardness in common wheat, and exert a strong impact on several quality traits such as yield and granularity of flour, starch damage and water absorption, rheological and baking properties. Effects of grain texture on pastamaking and breadmaking quality were evaluated in soft-textured durum wheat lines (SDLs) as compared with their hard durum sister lines (HDLs). SDLs accumulated puroindolines on their starch granules and showed SKCS values significantly lower than those of their hard-textured counterparts lacking Pin-A and Pin-B. The average flour extraction rate of SDL was about 23% higher than that of HDL. Increasing kernel softness significantly affected rheological parameters, whereas spaghetti cooking quality was unaffected by kernel hardness. Loaf volume exhibited a 10% increase associated with kernel softening. In order to reduce plant height, soft durum lines with the lowest SKCS indexes were further crossed with durum wheat cv. Simeto and 17 F6 progeny lines were evaluated in terms of stability for their short height, soft texture and gluten quality. Modulation of kernel texture in durum wheat was obtained as well by transgenic approach by inserting vromindoline genes from oats. Finally soft textured durum wheat were used in crosses with Triticum aestivum with the aim to obtain extra-soft common wheats that may supply breeders with a broader range of kernel texture.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)